If it's not what You are looking for type in the equation solver your own equation and let us solve it.
z in (-oo:+oo)
6 = z+2/3 // - z+2/3
6-z-(2/3) = 0
6-z-2/3 = 0
16/3-z = 0 // - 16/3
-z = -16/3 // * -1
z = 16/3
z = 16/3
| 0.3-(2x+9)=0.6x | | 16x-72=18x+14 | | 56+3x-24-63=45x-14x+22 | | p=1/2(2x)(x+3) | | 13x+14y=178 | | .1-.01(x+2)=-.03(4-x) | | 9x+10/7=4x+1/2 | | 25x-10=3x-9 | | 5x+6x-8x-5=13 | | 2-6m-4m=-18 | | 1-4x+4=2x+11-4x | | 40x+20-15=20x+10 | | -3(8x-4)= | | 9+9+14= | | 3x-8+x=40 | | 13(s+12)= | | (x/5)-(1/x)=(3x+4/15) | | 20x+15-10x+50=8x-24 | | 27-7x=-6x | | x^2-4x+4-75=0 | | 3=33-11 | | -v+1=4 | | -2r-15=8r-7r | | 6(-6x-4)=-60 | | 0.25(8y+4)-17=-0.5(2y-8) | | 2(4x+8)=3(2x-10) | | 1/4(8y+4)-17=-1/2(2y-8) | | 3(x+3)=5x-7 | | 4/35=h/50 | | 12x+15= | | -4(8-5n)+8=-1 | | Y=8X-70 |